2011
DOI: 10.7150/ijms.8.711
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Ventricular Meningioma Presenting with Intraventricular Hemorrhage: A Case Report and Literature Review

Abstract: Lateral ventricular meningiomas presenting with primary intraventricular hemorrhage are extremely uncommon. We report here a case of primary intraventricular hemorrhage attributable to a lateral ventricular meningioma. This case concerns a 46-year-old female patient who presented with sudden onset of headache. Computed tomography (CT), computed tomography angiography (CTA) and magnetic resonance imaging (MRI) examinations showed hemorrhage from a ruptured tumor mass, which was pathologically confirmed as a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
(26 reference statements)
0
18
0
1
Order By: Relevance
“…Wakai et al [ 2 ] reported the incidence of meningioma with the sign of hemorrhage in pathologic study as 1.3%, but clinically symptomatic hemorrhages are supposed to be much more uncommon [ 1 , 3 ]. Two large study of meningiomas by Cushing et al and Hoessly et al looked at 313 and 280 cases, respectively, and none of the cases showed clinically significant hemorrhage at presentation [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wakai et al [ 2 ] reported the incidence of meningioma with the sign of hemorrhage in pathologic study as 1.3%, but clinically symptomatic hemorrhages are supposed to be much more uncommon [ 1 , 3 ]. Two large study of meningiomas by Cushing et al and Hoessly et al looked at 313 and 280 cases, respectively, and none of the cases showed clinically significant hemorrhage at presentation [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meningiomas causing intraventricular hemorrhage are infrequent. [5][6][7] Most of these tumors arise in the lateral ventricle, and > 90% occur in the trigone. Reviewing the literature, we found 10 cases of sphenoid wing meningiomas presenting with hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Visual symptomatology is most often related to the accompanying secondary optic atrophy or hydrocephalus. Rarely hemorrhage may be a revealing sign [9,10].…”
Section: Discussionmentioning
confidence: 99%